2017
DOI: 10.1021/acs.jnatprod.7b00591
|View full text |Cite
|
Sign up to set email alerts
|

neo-Clerodane Diterpenoids from Salvia polystachya Stimulate the Expression of Extracellular Matrix Components in Human Dermal Fibroblasts

Abstract: Eleven neo-clerodane diterpenoids (1-11) including the new analogues 1, 2, and 10, and 3',5,6,7-tetrahydroxy-4'-methoxyflavone (12) were isolated from the aerial parts of Salvia polystachya. Polystachyne G (1) and 15-epi-polystachyne G (2) were isolated as an epimeric mixture, containing a 5-hydroxyfuran-2(5H)-one unit in the side chain at C-12 of the neo-clerodane framework. Polystachyne H (10) contains a 1(10),2-diene moiety and a tertiary C-4 hydroxy group. The structures of these compounds were established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…We postulated that compounds present on Sp extract, besides lowering the stress oxidative-induced damage, might allow adaptations on gene regulation. For example, aerial parts of Sp contain eleven neo-cleorodane difepenoids; some of these compounds augmented the expression of extracellular matrix components (e.g., genes codifying type I, II, and V collagens and elastin) [57], which are critical for vascular basement membrane function and play a central role in cerebrovascular diseases [58]. Compounds in S. mitiorrhiza can also inhibit the expression of adhesion molecules in vascular endothelium and in leukocytes that help to prevent the development of vascular damage induced by ischemia and reperfusion [59].…”
Section: Sp Extract Protects Against Cerebral Ischemia-induced Damagementioning
confidence: 99%
“…We postulated that compounds present on Sp extract, besides lowering the stress oxidative-induced damage, might allow adaptations on gene regulation. For example, aerial parts of Sp contain eleven neo-cleorodane difepenoids; some of these compounds augmented the expression of extracellular matrix components (e.g., genes codifying type I, II, and V collagens and elastin) [57], which are critical for vascular basement membrane function and play a central role in cerebrovascular diseases [58]. Compounds in S. mitiorrhiza can also inhibit the expression of adhesion molecules in vascular endothelium and in leukocytes that help to prevent the development of vascular damage induced by ischemia and reperfusion [59].…”
Section: Sp Extract Protects Against Cerebral Ischemia-induced Damagementioning
confidence: 99%
“…From the leaves, neo-clerodane diterpenes, such as polystachynes A–H, 15-epi-polystachine G, salvifiline A and C, 15-epi-salvifiline A, and linearolactone, and the flavone 3’,5,6,7-tetrahydroxy-4’-methoxyflavone, were isolated [ 33 , 34 ]. Among these, the diterpene linearolactone exhibited antiprotozoal activity in Entamoeba histolytica and Giardia lamblia [ 35 ]; moreover, polystachynes B and G, linearolactone and 15-epi-salvifiline A increased the gene expression of elastin and the type I, III, and V of collagens [ 36 ]. Although several species of the Salvia genus have been reported to have antidiabetic properties, there are no scientific reports that support S. polystachya ’s effects on hyperglycemia yet.…”
Section: Introductionmentioning
confidence: 99%
“…The structures of the isolated compounds were established by the analyses of their NMR spectroscopic and MS spectrometric data and were compared with those described in the literature (Nagao et al 2002;Gecibesler et al 2019). Curiously, during the isolation procedure, sesquiterpenoids and diterpenoids were not isolated as is common in Salvia species (Bautista et al 2017;Fragoso-Serrano et al 2019). The subsequent evaluation of the antiprotozoal properties of isolates 1-3 showed that compounds 1 and 2 had moderate antiprotozoal activity against both protozoa, with IC 50 values of 40.4 (40.9-39.8) and 42.7 (43.1-41.8) μM against E. histolytica; and 61.6 (66.1-60.4) and 60.3 (62.1-59.4) μM against G. lamblia, respectively.…”
Section: Resultsmentioning
confidence: 99%